Effect of intrajejunal elemental diet perfusion on jejunal secretion of immunoglobulins, albumin, and hyaluronan in man. Issue 1 (January 1992) - Colombel, J F; Vaerman, J P; Hällgren, R; Dehennin, J P; Wain, E; Modigliani, R; Cortot, A
Abstract : The aim of this work was to study the jejunal secretion of immunoglobulins (Ig), albumin, and hyaluronan in response to jejunal perfusion of an elemental diet. A four lumen tube with a proximal occluding balloon at the angle of Treitz was used for jejunal perfusion in seven healthy volunteers (mean age 23 years). The length of the test segment was 40 cm. The jejunum was successively perfused with a control electrolyte solution for 80 minutes and with an elemental diet (containing 20.5 milligrams of free amino acids and 104.2 milligrams of oligosaccharides) for 100 minutes. The jejunal fluid concentrations of albumin, IgG, monomeric IgA (m-IgA), polymeric IgA (p-IgA), IgM, secretory component, and hyaluronan were measured and their jejunal outputs calculated. Within 20 minutes of starting perfusion with the elemental diet there was a significant increase in the secretion rates of albumin (x3.3), IgG (x5), M-IgA (x3.7), p-IgA (x2), IgM (x2), and secretory component (x1.6), but the hyaluronan secretion rate was not changed. The increase in m-IgA, p-IgA, IgM, and secretory component output suggests that intestinal perfusion of an elemental diet results in stimulation of secretory immunity. The increase in albumin and IgG output probably reflects a nutrient induced leakage from the plasma compartment.